Analisis Dampak Fatherless Terhadap Etika Remaja Awal di Kecamatan Medang Deras - Saragih, Yuli Erwina; Metia, Cut (UIR Press, 2024)
The purpose of this study is to analyze the negative and positive impact of fatherlessness on the ethics of early adolescents in MedangDeras District. The method used in this study uses a qualitative method with a phenomenological approach. The selected data collection techniques include observation, interviews, and documentation. The research subjects consisted of 4 teenagers. Qualitative data analysis The validity of the data is achieved through the application of the source triangulation method. The data analysis used is an interactive analysis model that includes collection, reduction, presentation, and conclusion drawn. The results of the study show that the impact of fatherlessness on early adolescent ethics is negative and positive. The negative impact is feeling difficult, lack of emotional control, behavioral deviations, economic problems and feelings of fear. Positive impacts include independent learning, closeness to mothers, increased environmental fit, and responsibility. As a result of fatherlessness, adolescent ethics are declining, making adolescents experience difficulties in socializing, withdrawing, causing aggressive behavior, deviations in dress, and ethical violations in communication.